Laws and Guidelines for Muamalah Through Social Media: Sharia Perspectives in the Digital Era - Achmad Ridwan; Widya Cholid Wahyudin; Oman Fathurohman SW; Dandy Okorontah (Walidem Institute and Publishing (WIP), 2025)
Objective: This study is to systematically examine the laws and guidelines of mutual understanding through social media from the perspective of Islamic law, in response to the rapid development of economic and social interaction on digital platforms. Theoretical framework: this research is based on sharia principles taken from the Qur'an and Hadith, as well as Islamic ethical values such as honesty (shidq), Amanah, tabayyun, and clarity of the contract. Literature review: This research includes primary sources such as the Qur'an and Hadith, as well as secondary sources in the form of jurisprudence, scientific articles, MUI fatwas, and laws and regulations relevant to digital muamalah. Methods: This study uses a qualitative approach with the library research method, through an in-depth analysis of literature related to Islamic law and interaction on social media. Results: This study shows that muamalah through social media is permissible in Islam as long as it does not contradict sharia principles such as the prohibition of riba, gharar, maysir, and tadlis. This research also emphasizes the importance of applying Islamic ethics in digital interactions. Implications: This study highlights the need to increase education about digital fiqh muamalah fiqh, collaboration between scholars, the government, and digital platforms, as well as the preparation of regulations that are adaptive to technological developments to minimize sharia violations on social media. Novelty: this research lies in the systematization of comprehensive sharia guidelines in muamalah on social media, which can be a practical reference for Muslims in interacting digitally responsibly and by religious teachings.